Knowledge and practice of self-care nurse service Pediatrics, Hospital Nacional Guillermo Almenara Irigoyen, 2013 - Manturano Velásquez, Zenaida Doylitt (2019)
Objective: To determine the relationship between knowledge and practice self-care nurse in the pediatric wardof the National Hospital Guillermo Almenara Irigoyen. Methods: The research is correlational, descriptivequantitative, non experimental design, cross-section; the sample consisted of 45 nurses. Two differentquestionnaires adapted by the researcher, for the area of practical questions “Rating Scale Capacity AgencySelf-Care” developed by Ysenberg and Evers, translated and validated in Spanish by Esther was used was usedfor data collection Gallegos; and to the knowledge variable researcher developed a questionnaire, which wasvalidated by experts in the field. Results: The results obtained were that 42.2% of the sample is within the rangeof not knowing about self and displays an appropriate practice on it; likewise 26.7% is in the range of properunderstanding and practice self-care; there is also a 8.9% of the nurse who despite not knowing about the self hasadequate self-care practices. Applying statistical chi square test the relationship of the variables was significant p= 0.009, indicating that there is significant relationship between both variables. Conclusion: There is significantrelationship between knowledge and practice that the nurse has on yourself.